2001
DOI: 10.1007/s002610000139
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hepatocellular carcinoma after treatment with transcatheter arterial chemoembolization: comparison of Lipiodol-CT, power Doppler sonography, and dynamic MRI

Abstract: Of the three modalities, dynamic MRI was the best for evaluating the efficacy of TACE in the treatment of HCC. We also found that superficial lesions of the right lobe are good candidates for PD sonography. However, high signals on precontrast MR images, motion artifacts, and ultrasonic attenuation remain key limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 23 publications
0
76
0
4
Order By: Relevance
“…However, due to partial volume or beam-hardening artifact, the high attenuation density of the iodized oil can limit the accuracy of CT in depicting a small viable tumor portion in or adjacent to the lesion (4 -6). To avoid the interference of accumulated iodized oil, Doppler ultrasonography or dynamic MRI has been used as an alternative to dynamic CT (7)(8)(9)(10)(11); however, inherent ultrasonic attenuation or T1-weighted hyperintensity of hemorrhagic-necrotic changes still affects the correct interpretation of contrast-enhanced viable tumor tissue.…”
mentioning
confidence: 99%
“…However, due to partial volume or beam-hardening artifact, the high attenuation density of the iodized oil can limit the accuracy of CT in depicting a small viable tumor portion in or adjacent to the lesion (4 -6). To avoid the interference of accumulated iodized oil, Doppler ultrasonography or dynamic MRI has been used as an alternative to dynamic CT (7)(8)(9)(10)(11); however, inherent ultrasonic attenuation or T1-weighted hyperintensity of hemorrhagic-necrotic changes still affects the correct interpretation of contrast-enhanced viable tumor tissue.…”
mentioning
confidence: 99%
“…Median ADC before and after TACE is significantly increased among patients with HCC (8,9). Iodized-oil CT is widely used to confirm HCC response to TACE immediately after TACE (14)(15)(16). However, to the best of our knowledge, ADC has not been correlated to the degree of effectiveness of TACE against HCC as estimated by iodized-oil CT.…”
Section: Introductionmentioning
confidence: 70%
“…A variety of imaging techniques have been introduced for the evaluation of therapeutic efficacy after performing TACE and RFA for HCC (2)(3)(4)(5). Several investigators suggested that dynamic MRI using 1.5T Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the foregoing features, an area with moderate hyperintensity on T2-weighted MR images and hypointensity on gadoxetic acid-enhanced hepatobiliary phase MR image compared with surrounding liver parenchyma was considered a viable tumor based on previous reports (3,5,6,13). The criteria for viable tumors on CT and gadoxetic acid-enhanced MRI after TACE were similar to those for viable tumors after RFA, and these criteria were based on previous reports (2,4,6,(16)(17)(18).…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation